Menjadi penggerak di tengah keterbatasan: Peran Guru sebagai agen perubahan di SMA Negeri 1 Danau Seluluk - M. Sahlani Budi; Novia Dwi Lasenia; Tonich Uda (Edunomics Journal, 2026)
This study aims to analyze how teachers at SMA Negeri 1 Danau Seluluk carry out their roles as change agents amidst various limitations in facilities, infrastructure, and the broader context of limited-access schools. Using a descriptive quantitative approach, the research involved 10 teachers selected through purposive sampling. The research instrument consisted of a 1–5 Likert-scale questionnaire covering three main variables: the teacher’s role as an innovator, motivator, and learning facilitator. The findings indicate that all variables fall within the high category, with an overall mean score of 4.27. These results suggest that teachers are able to drive positive change despite constraints related to resources and access. The study underscores the importance of teacher agency and offers several recommendations to strengthen the role of teachers in schools located within limited-access regions